1978
DOI: 10.1002/aja.1001510305
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal development of ependyma in the third ventricle of male and female rats

Abstract: Ependyma in the third ventricle of developing male and female rats (0, 5, and 10 days postpartum) were compared with those of sexually mature male rats by means of scanning electron microscopy (SEM) and transmission electron microscopy (TEM). No sexual dimorphism appeared in the developmental group. At all ages the dorsolateral ventricular wall was composed of ciliated ependymal cells, while ependymal cells of the ventrolateral wall exhibited apical microvilli and bleb-like irregularities. While SEM revealed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…Injection of radiolabeled thymidine ( 3 H-thymidine) into pregnant rat dams identified that neurons of most hypothalamic nuclei originate between E14 and E18 within the ventricular zone of the hypothalamic third ventricle (6,7,10,20) and that these postmitotic neurons subsequently migrate laterally to populate the surrounding nuclei (10). Morphological changes similar to those reported here, in terms of ventricular thinning over the first postnatal weeks, have been reported previously (44) and suggested that this change may be the result of neuronal migration away from the ventricular zone. In addition, there appears to be a decline in the number of cells both within the ventricular region and also the surrounding ARC and VMH areas with increasing age.…”
Section: Discussionsupporting
confidence: 82%
“…Injection of radiolabeled thymidine ( 3 H-thymidine) into pregnant rat dams identified that neurons of most hypothalamic nuclei originate between E14 and E18 within the ventricular zone of the hypothalamic third ventricle (6,7,10,20) and that these postmitotic neurons subsequently migrate laterally to populate the surrounding nuclei (10). Morphological changes similar to those reported here, in terms of ventricular thinning over the first postnatal weeks, have been reported previously (44) and suggested that this change may be the result of neuronal migration away from the ventricular zone. In addition, there appears to be a decline in the number of cells both within the ventricular region and also the surrounding ARC and VMH areas with increasing age.…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that in early postnatal period, developmental processes continue in ependymal cells of the third ventricle of the rat (Bruni, 1998;Walsh et al, 1978), the central canal of the mouse (Sturrock, 1981) and the lateral ventricle of the rabbit (Abbate et al, 1993). In cats ependyma forms the complete lining of the surface of the central canal until 2 or 3 months after birth in domestic cats (Bohme, 1988).…”
Section: Discussionmentioning
confidence: 97%
“…of the spinal cord, are very active in cell proliferation in fetal and newborn rat but not in adult rat (Bruni et al, 1985). These cells differentiate until a certain period after birth (Bruni et al, 1983;Roessmann et al, 1980;Walsh et al, 1978). For example, ependymal cells of rat brain show many mitotic figures until 10 days after birth (Walsh et al.…”
Section: Discussionmentioning
confidence: 99%